EP1194 Primary vaginal leiomyosarcoma: a case report with complete morphological, immunohistochemical and ultrastructural study. (1st November 2019) - Vizza, E; Petrozza, V; Natale, P; Certelli, C; Battaglione, E; Corrado, G; Familiari, G; Heyn, R
Abstract : Introduction/Background: Primary vaginal leiomyosarcomas (LMS) are rare, recurrent tumours with an unknown etiology; the prognosis is poor and there is no consensus guideline on their management. A nodular, 25 x 23 x 28 mm-mass, infiltrating the urethra but not the rectovaginal septum, was found in a 58-year-old previously hysterectomized woman. A biopsy showed a LMS of the vagina and an anterior pelvic exenteration was performed. Methodology: The sample was fixed and prepared for light microscopy, transmission and scanning electron microscopy. An immunohistochemical analysis was performed. Results: The results confirmed a LMS of the vagina that was positive for vimentin, alpha-smooth muscle actin, caldesmon, desmin, p16 and p53. Light microscopy revealed that the mass contained a storiform pattern of spindle-shaped cells with blunt-ended nuclei. Cells were arranged in interwoven fascicles within a dense and richly vascularised stroma, suggesting an active neoangiogenesis. The histopathological analysis revealed a coagulative focal necrosis and low to moderate mitotic indexes, about 1–4/10 high power fields (HPF). Scanning Electron Microscopy (SEM) evidenced a dense collagenous stroma with numerous small blood vessels. Transmission Electron Microscopy (TEM) showed invasive neoplastic and pleomorphic cells with complex labyrinthic cytoplasm projections. Tumoral cells contained paranuclear crowds of dilated mitochondria, free ribosomes and a well-developed rough endoplasmic reticulum. There were atypical mitotic figures. Blood vessels were usually lined by a high and reactive endothelium. Conclusion: The histopathological and ultrastructural analyses confirmed the malignancy of this tumor. Best outcomes occur when the tumour is small, localized, and can be removed surgically with wide, clear margins, as in this case. As there are different kinds of malignant mesenchymal tumours, biopsy followed by immunohistochemistry and electron microscopy still represents a good diagnostic choice. Disclosure: Nothing to disclose